Fluorescence and molecular simulation studies on the interaction between imidazolium-based ionic liquids and calf thymus DNA - Jumbri, Khairulazhar; Kassim, Mohd Azlan; Mohamad Yunus, Normawati; Abdul Rahman, Mohd Basyaruddin; Ahmad, Haslina; Abdul Wahab, Roswanira (MDPI, 2020)
This work presents a molecular level investigation on the nature and mode of binding between imidazolium-based ionic liquids (ILs) ([Cnbim]Br where n = 2, 4, 6) with calf thymus DNA. This investigation offers valuable insight into the mechanisms of interactions that can affect the structural features of DNA and possibly cause the alteration or inhibition of DNA function. To expedite analysis, the study resorted to using molecular docking and COnductor like Screening MOdel for Real Solvents (COSMO-RS) in conjunction with fluorescence spectroscopic data for confirmation and validation of computational results. Both the fluorescence and docking studies consistently revealed a weak interaction between the two molecules, which corresponded to the binding energy of a stable docking conformation in the range of −5.19 to −7.75 kcal mol−1. As predicted, the rod-like structure of imidazolium-based ILs prefers to bind to the double-helix DNA through a minor groove. Interestingly, the occurrence of T-shape π-π stacking was observed between the amine group in adenine that faces the aromatic ring of imidazole. In addition, data of COSMO-RS for the interaction of individual nucleic acid bases to imidazolium-based ILs affirmed that ILs showed a propensity to bind to different bases, the highest being guanine followed by cytosine, thymine, uracil, and adenine.